The applicability of archive identification in personal archives: a reflection - Troitino, Sonia [UNESP]; Fonseca, Gabrieli Aparecida da [UNESP] (Ibersid Network, 2016)
The applicability of archival identification to personal archives is explored. The goal is to evidence the role of archival identification in the organization method of personal papers. In this sense, the hypothesis is explored that archival identification contributes largely to ensure to the appropriate treatment and custody of personal records, because it involves a deep study of the genesis of the archive, with the purpose to investigate its provenance, retrieve and show its inherent elements in their various levels
Keywords: Archival identification; Archival organization; Personal papers